A afirmação da angolanidade em ondjaki: uma análise do universo da alegoria em os transparentes - CARNEIRO, Vanessa Soeiro (2018)
The aim of this study is analyze the novel Os transparentes (The transparents), by the Angolan writer Ondjaki, from the perspective of the allegory, due to its influence in the narrative narrowness through bibliographical-qualitative research using the deductive mmethod. The relationships between allegory, metaphor and symbol and a re-reading of certain stereotypes concerning the African Literature of Portuguese expression will also be the focus of our studies. The book has great importance in the sociopolitical and cultural context of the contemporary Angola for portraying, in a realistic way, the daily life of the less privileged population and its most unusual survival schemes. For such analysis, Antoine Compagnon, Clive Staples Lewis, Edward Lopes, Flávio Kothe, João Adolfo Hansen and Walter Benjamin serve as theoretical support regarding the concept of allegory. As for the contextualization of the African Literature of Portuguese expression, more particularly Angola, the studies of Benjamin Abdala Junior, Carmen Secco, Edward Said, Inocência Mata, Maurício Silva, Pires Laranjeira, Rita Chaves, Stuart Hall and Tânia Macedo base our analysis. Among the results of this research, the most important is the realization that the main allegory in the novel is physical transparency of Odonato and that it represents his social transparency as well as the transparency of his friends, Luanda, Angola and of Africa itself.